2021
DOI: 10.3389/fmed.2021.663694
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Profile of Viral Meningitis Infections Among Patients in Qatar (2015–2018)

Abstract: Background: Little is known about the etiology of meningitis in the MENA region, including Qatar. Viral agents are considered the major cause for meningitis worldwide. Here, we present primary data about the etiology and clinical and demographic characteristics of viral meningitis (VM) in Qatar between 2015 and 2018.Methods: We retrospectively collected data from Hamad Medical Corporation (HMC), which provides about 80% of healthcare services in Qatar. Data were collected for the period between 2015 and 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
7
16
1
1
Order By: Relevance
“…The World Health Organization identified dengue, viral encephalitis, diarrheal illness, enteric fever, pneumonia, and meningitis as the diseases most vulnerable to climate change, and expected a significant increase in incidence in tropical nations ( 36 ). Our impression of the seasonality of VM is consistent with overall awareness of higher incidence in warm months and in line with previous reports ( 37 , 38 ). As far as we know, this is the first study in Central Asia that focuses on VM epidemiology and investigates the association between disease and three meteorological factors.…”
Section: Discussionsupporting
confidence: 93%
“…The World Health Organization identified dengue, viral encephalitis, diarrheal illness, enteric fever, pneumonia, and meningitis as the diseases most vulnerable to climate change, and expected a significant increase in incidence in tropical nations ( 36 ). Our impression of the seasonality of VM is consistent with overall awareness of higher incidence in warm months and in line with previous reports ( 37 , 38 ). As far as we know, this is the first study in Central Asia that focuses on VM epidemiology and investigates the association between disease and three meteorological factors.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, VZV-associated PVM cases were reported even among children who were vaccinated against the disease (115). Epstein Barr virus (EBV) was also documented in many reports as a significant causative agent of PVM (73,116,117). Meningitis due to EBV was described as a self-limiting neurological disorder with residual pathological outcomes detected only in meager cases (117).…”
Section: Herpesvirusesmentioning
confidence: 99%
“…The susceptibility to VM was seen depending on some risk factors, such as the patient's age, immunity status, and concomitant other viral infections like HIV (1,53,93,103). VM was known to affect the different age groups of people, with more severe clinical consequences detected among pediatric patients than adults (73). Newborns and infants are more likely to develop more acute and critical PVM cases than older children since they are not equipped with mature immune apparatus (7,11,74).…”
Section: Epidemiologymentioning
confidence: 99%
“…This is in line with a previous study (732/6,705, 10.9%, 2015–2019), which was confirmed using the FTD-viral meningitis diagnostic kit. [ 13 ] Compared to our study, authors from other countries found higher rates of viral agents, including Brazil (44/70, 62.9%, 2010 and 2013), which was confirmed using the SYBR qPCR, [ 14 ] Lebanon (205/252, 82.7%, 2008–2016) [ 15 ] and the United Arab Emirates (34/92, 37%; 2000–2005), [ 16 ] which were confirmed using laboratory tests (clinical grounds and by exclusion of bacterial meningitis). The differences in prevalence between the different studies could be attributed to the test method and population of patients, and factors such as age group, sampling time, sample storage and transport, season, sporadic cases or an outbreak, and the high variability of the viral genes or other viral infections.…”
Section: Discussionmentioning
confidence: 99%